2015
DOI: 10.11113/jt.v74.4709
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phenol from Wastewater by Supported Liquid Membrane Process

Abstract: Phenol is considered a pollutant in the environment due to its toxicity and carcinogenic effect. Supported liquid membrane (SLM) is a good and promising technology for the removal of phenol from wastewater because it provides maximum driving force for the separation of targeted solute and simultaneous extraction and stripping process which lead to excellent separation. In this research, kerosene and palm oil liquid membranes were used as liquid membrane phase, aqueous phenol as the feed phase and aqueous sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Also, it is observed that at this ratio the phase separation time of the mixed solution is significantly reduced. It is expected that by adding kerosene to palm oil, the viscosity of palm oil will be reduced hence it will increase the distribution coefficient of solutes and will influence the solvent extraction kinetics [10]. This is because kerosene contains a higher number of carbon atoms, which resulted in higher hydrophobicity and it is much less soluble in water compared to palm oil [18].…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it is observed that at this ratio the phase separation time of the mixed solution is significantly reduced. It is expected that by adding kerosene to palm oil, the viscosity of palm oil will be reduced hence it will increase the distribution coefficient of solutes and will influence the solvent extraction kinetics [10]. This is because kerosene contains a higher number of carbon atoms, which resulted in higher hydrophobicity and it is much less soluble in water compared to palm oil [18].…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Meanwhile, the phenol-TBP complexes reacted with the aqueous sodium hydroxide solution, leading to the formation of sodium phenolate, TBP molecules and water. Triglyceride and TBP molecules were expected to retain in the solvent to form complexes with excess phenols [10]. The sodium phenolates formed from the reaction are expected not to diffuse back into the solvent.…”
Section: Effect Of Stripping Agents Type In Stripping Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of phenol recovery methods from wastewater is currently the concern of many researchers, in order to find solutions for phenol waste management (Ariesmayana, 2018;Sun et al 2017). Phenol waste treatment needs to be carried out with methods that are more practical, inexpensive, and fast (Othman et al 2015). One of the renewable methods that can be used to perform the separation and recovery of phenol is liquid membrane method (Refinel et al 2019;Kiswandono 2016;Yang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of wastewater for pollutant removal is very crucial since it can cause a threat to potable drinking water sources, fisheries, and recreational water bodies. Membrane technology [5][6], liquid membrane [7], and adsorption [8][9][10][11] are a few of the treatment techniques and technologies utilized to treat wastewater. However, certain technologies already in use still struggle to comply with the standard of discharge, the restrictions that have been set up, difficulty in scaling up, and come at a high cost.…”
Section: ■ Introductionmentioning
confidence: 99%